2003
DOI: 10.1161/01.res.0000075601.95738.6d
|View full text |Cite
|
Sign up to set email alerts
|

Hypercapnic Acidosis Activates K ATP Channels in Vascular Smooth Muscles

Abstract: Abstract-ATP-sensitive K ϩ channels (K ATP ) couple intermediary metabolism to cellular activity, and may play a role in the autoregulation of vascular tones. Such a regulation requires cellular mechanisms for sensing O 2 , CO 2 , and pH. Our recent studies have shown that the pancreatic K ATP isoform (Kir6.2/SUR1) is regulated by CO 2 /pH. To identify the vascular K ATP isoform(s) and elucidate its response to hypercapnic acidosis, we performed these studies on vascular smooth myocytes (VSMs). Whole-cell and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 46 publications
3
64
0
Order By: Relevance
“…RT-PCR analysis showed SUR2B mRNA to be ubiquitously expressed in diverse tissues, including the kidney , and also to be localized in rat vascular smooth muscle (Wang et al 2003) and rat mesangial cells (Szamosfalvi et al 2002). The SUR2 protein was shown to be expressed during development of the rat kidney (Hernandez-Sanchez et al 1997).…”
Section: Discussionmentioning
confidence: 98%
“…RT-PCR analysis showed SUR2B mRNA to be ubiquitously expressed in diverse tissues, including the kidney , and also to be localized in rat vascular smooth muscle (Wang et al 2003) and rat mesangial cells (Szamosfalvi et al 2002). The SUR2 protein was shown to be expressed during development of the rat kidney (Hernandez-Sanchez et al 1997).…”
Section: Discussionmentioning
confidence: 98%
“…5,6,30,31 Animal studies have shown hypercapnia activates K ATP channels in vascular smooth muscle, causing vasodilation. 32 Animal models have also suggested that nitric oxide plays a role in hypercapnic vasodilation. 2,30 However, human studies have shown that hypercapnia acts independently of nitric oxide to produce elevated CBF.…”
Section: Discussionmentioning
confidence: 99%
“…SUR2A is prominent in cardiomyocytes (Chutkow et al 1996;Inagaki et al 1996), whereas RT-PCR of SUR2B has revealed its ubiquitous distribution in various cells and tissues including cardiomyocytes (Isomoto et al 1996) and rat vascular smooth muscle (Wang et al 2003). Until now, there have been no unequivocal data establishing the precise cellular localization of SUR2A and SUR2B subunits in cardiac myocytes.…”
Section: Discussionmentioning
confidence: 99%